Nuclear phylogeny and hypothesized allopolyploidization events in the Subtribe Otachyriinae (Paspaleae, Poaceae). Issue 3 (3rd April 2019) - Acosta, Juan M.; Zuloaga, Fernando O.; Reinheimer, Renata
Abstract : Otachyriinae Butzin, one of the three subtribes within the Paspaleae tribe of grasses, includes seven genera and approximately 35 species. Interestingly, this subtribe comprises species with C3, C3 -C4 intermediate, and C4 photosynthesis. The circumscription of Otachyriinae has changed through time, and still varies among treatments in current use. The monophyly of this subtribe has been recovered in previous studies based on plastid markers. A phylogenetic study taking into account polyploidy and a low-copy nuclear gene (LCNG) is still lacking in Paspaleae. A phylogeny including data from a LCNG is paramount to uncover reticulated evolution within the group. The purpose of the present study was to reconstruct the evolutionary history of Otachyriinae, based on both chloroplast and LCNG DNA with a focus on polyploidization. Several incongruences between gene trees allowed us to explore relationships between diploid and polyploid taxa. Our study identified several promising topics for future studies: genetic allopolyploidy and autopolyploidy was here documented using the characteristic pattern of double-labelled gene trees. The molecular evidence indicates that at least 40% of species of Otachyriinae show phylogenetic signature of polyploidy (16 taxa appear double-labelled in the nuclear gene trees); furthermore, the results support an allopolyploid origin of at least nine taxa in the subtribe: Rugoloa polygonata, a species with unknown photosynthetic pathway, the proto-kranz species Steinchisma laxum and Rugoloa hylaeica, and the C3 species Hymenachne felliana, H. grumosa, H. hemitomon, H. donacifolia, H. pernambucense, and P. grande . Also, our results confirm that the C4 genus Anthaenantia is unambiguously monophyletic and show that Anthaenantia lanata is an autopolyploid. We recognized six genera within subtribe Otachyriinae: Anthaenantia, Hymenachne, Otachyrium, Plagiantha, Rugoloa, and Steinchisma . Finally, Panicum species with historically ambiguous placements, i.e. P. condensatum, P. grande, P. harleyi, P. leptachne, P. longum, and P. stagnatile were transferred to the genus Hymenachne .